The Impact of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior at PT. Victoria Nusa Bahari in Pangkalpinang - Febrianka, Defrans; Manullang, Rizal Ruben; Maharani, Yunita (MSJ : Majority Science Journal, 2024)
This study aims to analyze the influence of Servant Leadership and Organizational Commitment on Organizational Citizenship Behavior at PT Victoria Nusa Bahari. With a quantitative descriptive approach, this study involved 30 employees as respondents. Data were collected using a questionnaire applying the Likert measurement scale, and the analysis was performed through multiple linear regression with the help of Jeffreys's Amazing Statistics Program. The results of the study show that Servant Leadership has a significant influence on Organizational Citizenship Behavior, reflected by a significance value of 0.001 and a t-value of 5.694, which shows that servant leadership can encourage employees to behave more proactively and responsibly. In addition, Organizational Commitment also contributed significantly, with a significance value of 0.046 and a t-value of 2.094, indicating that the level of employee commitment to the organization had an effect on their involvement in civic behavior. Overall, the results show that both Servant Leadership and Organizational Commitment simultaneously have a significant influence on Organizational Citizenship Behavior, as evidenced by a significance value of 0.001 and an f-statistical value of 105.154. These findings emphasize the importance of supportive leadership roles and strong commitment to creating a positive work environment, as well as encouraging behaviors that support organizational success. This research is expected to be a reference for management in designing a more effective human resource development strategy.